Prevalence of high-risk human papillomavirus and cytological correlation in Gujarati women: implications for regional screening and vaccination strategies - Anand Shah; Bijal Patel; Majal Shah; Ruchi Arora; Chetna Parikh; Rohini Patel; Mohit Makwana; Samanta Satarupa; Vibha Vyas; Vaishali Ravani; Bijoy Kar; Abhilash V; et al. (BMC Women's Health, 2026)
Abstract Background High-risk human papillomavirus (hrHPV) infection is a major etiological factor for cervical cancer. HPV-16 and HPV-18 are the most prevalent oncogenic subtypes of cancer. Despite the availability of preventive strategies, cervical cancer remains a public health concern in India. This study aimed to estimate the prevalence of hrHPV genotypes and evaluate their association with cervical cytological abnormalities among women in Gujarat, India. Methods A cross-sectional study was conducted among 9,706 married women aged ≥ 30 years who attended community-based screening camps organized by the Gujarat Cancer Research Institute between January 2022 and December 2023. Cervical samples were collected for hrHPV DNA detection using the Roche COBAS ® 4800 platform, and liquid-based cytology was performed in hrHPV-positive cases. Statistical analysis was used to assess genotype-specific prevalence and associations with demographic and clinical variables. Results Overall, 4.9% ( n = 478) of women were hrHPV positive, with non-16/18 hrHPV types accounting for most infections (62.8%), followed by HPV-16 (18%) and HPV-18 (8.4%). Multivariate analysis revealed that early age at marriage, early age at first pregnancy, and abnormal cervical findings on examination were independently associated with hrHPV positivity, with malignant cervical findings showing the strongest association (adjusted odds ratio [OR] = 38.2; 95% CI: 3.4–429.1) and early pregnancy conferring an approximately fourfold risk (adjusted OR = 4.29; 95% CI: 2.31–7.96). HPV-16 showed the strongest association with cytological abnormality, particularly high-grade squamous intraepithelial lesion (HSIL) (OR = 6.18; 95% CI: 3.10–12.4), and HPV-16/18 co-infection further increased the risk of HSIL (OR = 31.33). Conclusion The predominance of non-16/18 hrHPV genotypes, combined with the strong HPV-16–HSIL association, underscores the importance of extended-genotype vaccination, genotype-informed screening, and reproductive health interventions (e.g., preventing early marriage and pregnancy). These findings directly support the WHO’s cervical cancer elimination strategy and call for policy actions to expand vaccine coverage, strengthen screening, and implement context-specific prevention strategies in Gujarat.